Three Minute Thesis (3MT) Competition - Returns to Campus - UiTM, IPSis (Institut Pengajian Siswazah (IPSis), 2023)
The Three Minute Thesis competition celebrates the exciting research conducted by Doctor of Philosophy students. Developed by The University of Queensland, 3MT cultivates students’ academic, presentation, and research communication skills. The competition supports their capacity to effectively explain their research in three minutes, in a language appropriate to a non-specialist audience. For over ten years, UiTM has organized a 3MT Competition consistently. Due to the COVID-19 pandemic, the 3MT competition was virtually organized beginning in the year 2020. On March 6, 2023, UiTM proudly hosted the Virtual 3MT Competition, inviting 22 competitors to compete.